A Review of Domestic Violence Criminology and the Academy's Women's Program as a Sustainable Prevention Effort - Tiyo Saputra; Sadrianor Sadrianor; Ananda Zakiyyah Salzabillah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This journal aims to provide an explanation of Article 5 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence which states that every person is prohibited from committing domestic violence against people within their household by means of: physical violence, psychological violence, sexual violence. and/or household neglect. In reality, even though there is Law Number 23 of 2004 concerning the Elimination of Domestic Violence, domestic violence still occurs frequently. The purpose of writing this article is to explain the factors that cause domestic violence and the suitability of the Perempuan Academy program as a sustainable non-penal effort to tackle domestic violence and its obstacles in Kel. Karang Anyar, Samarinda City. The data in this article was obtained from secondary data by conducting library research and reviewing textbooks and statutory regulations. The primary data in this article was obtained by carrying out data collection techniques and also interviews with a number of respondents and informants. The results of this research show that the factors that cause domestic violence are economic inequality and the community's lack of knowledge about domestic violence. Efforts to reduce domestic violence in Kel. Karang Anyar has been carried out in various ways, one of which is through mediation and through the Perempuan Academy which is appropriate as a sustainable non-penal effort. The obstacles faced in implementing this program are the aspect of activity support tools which are considered to be less than optimal. The factors that cause domestic violence resolutions do not reach the courts are because victims do not want to report them for various reasons. Meanwhile, efforts that can be made by law enforcement officials are repressive and preventive efforts by providing education about domestic violence. It is recommended that all relevant parties, including the police, legal aid institutions, government and society, continue to increase integrated cooperation in dealing with domestic violence.